2016
DOI: 10.3892/ol.2016.4142
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the galectin-9-Tim-3 pathway in glioma tissues is associated with the clinical manifestations of glioma

Abstract: Abstract. Glioma is known to induce local and systemic immunosuppression, which inhibits antitumor T cell responses. The galectin-9-Tim-3-pathway negatively regulates T cell pathways in the tumor immunosuppressive environment. The present study assessed the expression of Tim-3 and galectin-9 in glioma patients, and evaluated the association between the expression of Tim-3 and galectin-9 with clinical characteristics. The present study identified that Tim-3 expression was significantly increased in peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 28 publications
(30 reference statements)
9
62
0
Order By: Relevance
“…Five of the samples showed TIM-3–positive lymphocytes, four revealed a tumor cell staining pattern, and two were suspicious for TIM-3 positivity on microglia or other unidentified lysosome-containing immune cells. The IHC results are evidence that TIM-3 is expressed in human glioblastoma multiforme, and taken together with studies confirming Gal-9 expression on glioma tumor cells (14), these findings suggest that TIM-3 blockade may be an effective immunotherapeutic strategy in glioblastoma multiforme and provide a rationale for clinical translation of anti-TIM-3 therapies.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Five of the samples showed TIM-3–positive lymphocytes, four revealed a tumor cell staining pattern, and two were suspicious for TIM-3 positivity on microglia or other unidentified lysosome-containing immune cells. The IHC results are evidence that TIM-3 is expressed in human glioblastoma multiforme, and taken together with studies confirming Gal-9 expression on glioma tumor cells (14), these findings suggest that TIM-3 blockade may be an effective immunotherapeutic strategy in glioblastoma multiforme and provide a rationale for clinical translation of anti-TIM-3 therapies.…”
Section: Discussionsupporting
confidence: 52%
“…However, the presence of TIM-3 in human glioblastoma multiforme has not yet been clearly confirmed by IHC. A recent study by Liu and colleagues found that Gal-9 (the activating ligand for TIM-3) was expressed at increased level in glioma patients’ brain tissues as compared with noncancerous tissue from control patients (14). Furthermore, Gal-9 expression was significantly higher in grade 4 gliomas than in lower grade gliomas (grades 2–3), and levels of expression were associated with TIM-3 expression on CD4 and CD8 TILs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that ligands of these proteins are overexpressed in GBM cells, i.e. PD-L1 45 , galectin-9 46 , they constitute valuable targets to overcome the immunosuppressive nature of GBM and improve the efficacy of immunotherapeutic strategies for GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the available results suggest that galectin-9 expression is frequently altered when comparing tumor tissue with normal tissue (29). In addition, one study supports the hypothesis that galectin-9 is involved in several aspects of tumor progression (30).…”
Section: Discussionmentioning
confidence: 75%